Language of horror: A syntactic analysis of audience reviews on letterboxd for the conjuring: Last rites - Patrick Carlos D. Famanilay; Tammy Arielle A. Gania; Agathalia Venice M. Naguit; Rodolfo P. Dizon Jr (Journal of Education, Social & Communication Studies, 2026)
This study examined the syntactic structures used in audience reviews of The Conjuring: Last Rites on Letterboxd, focusing on how syntax contributed to evaluation, persuasion, and coherence in digital film discourse. Using Systemic Functional Linguistics (SFL), 20 English-language reviews were analyzed, segmented into clauses, and interpreted through Halliday’s ideational, interpersonal, and textual metafunctions. Findings revealed that simple and coordinated sentences dominated the corpus, reflecting reviewers’ preference for clarity, immediacy, and a conversational tone, while complex structures appeared less frequently. Syntactic analysis showed that evaluative stance was conveyed through declarative clauses, modality, and intensifiers, whereas occasional exclamatives and interrogatives heightened emotional expression. Syntax not only articulated judgments but also enhanced persuasive impact by signaling certainty, emphasis, and personal engagement. Coherence was maintained through consistent use of topical themes, conjunctions, and cohesive devices, which structured a clear progression of ideas. These patterns demonstrated that even in informal digital contexts, syntax remained central to organizing meaning and shaping readers’ interpretations. Overall, the study highlighted the importance of examining syntax in understanding how audiences constructed and negotiated meaning within online film reviews.